A sense of belonging at university: student retention, motivation and enjoyment. Issue 3 (16th March 2022) - Pedler, Megan Louise; Willis, Royce; Nieuwoudt, Johanna Elizabeth
ABSTRACT: A sense of belonging is important as it incorporates feelings of being valued, included and accepted at university. Research suggests that higher education students who have a greater sense of belonging tend to have higher motivation, more academic self-confidence, higher levels of academic engagement and higher achievement. This article presents findings from a questionnaire ( n = 578) that was developed to explore the relationships between university students' sense of belonging and student retention. The current study found a significant difference in the level of belonging between first-generation students and students whose parents had both completed university. Additionally, students who frequently considered leaving university without completing their degree (i.e. dropping out) had a significantly lower sense of belonging than students who did not. Finally, university students with a higher sense of belonging reported higher motivation and enjoyment in their studies whereas students who reported lower levels of belonging reported lower levels of motivation and enjoyment. This study highlights that university students' sense of belonging is of high importance to higher education institutions as it increases students' academic motivation and enjoyment in their studies, which can impact on student achievement and reduces the likelihood of students considering leaving university before completing their studies, thus contributing to student retention.